ANTIAGING CREAM OF ZINGIBER MONTANUM RHIZOME EXTRACT THROUGH IN VITRO INHIBITION ACTIVITY OF ELASTASE AND TYROSINASE ENZYME - WULANSARI, ENDANG DWI; WULANDARI; SARI, FRANSISKA MIRANDA PUSPITA; IKASARI, ENDANG DIYAH (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to evaluate the elastase and tyrosinase inhibitory activity of bangle (Zingiber montanum) rhizome extract and to develop a cream formulation based on the extract as an anti-aging cosmetic preparation. Methods: Extraction of Z. montanum rhizome was carried out using 95% ethanol as the solvent, considering its effectiveness in dissolving terpenoid and phenylbutanoid compounds. Metabolite profiling was conducted using Gas Chromatography-Mass Spectrometry (GC-MS) to determine the compound composition of the extract. The anti-aging potential was assessed by in vitro testing for elastase and tyrosinase inhibitory activities. A cream formulation was then developed using extract concentrations of 0.5%, 2.5%, and 5%, and evaluated for physical characteristics including organoleptic properties, emulsion type, homogeneity, pH, viscosity, spreadability, and adhesion. Results: GC-MS analysis identified 27 compounds in the extract, including terpinen-4-ol and members of the phenylbutanoid group. The bangle rhizome extract demonstrated tyrosinase inhibitory activity with an IC₅₀ of 1333.44 mg/L, compared to kojic acid (IC₅₀ = 480.72 mg/L). The elastase inhibitory activity showed an IC₅₀ of 919.44 mg/L, while the standard gallic acid had an IC₅₀ of 325.25 mg/L. The cream formulations prepared with the extract exhibited acceptable physical properties for topical application, including a yellow color with a distinctive aroma, oil-in-water (o/w) emulsion type, and appropriate homogeneity, pH, viscosity, spreadability, and adhesion. Conclusion: Based on the results, Z. montanum rhizome extract exhibits potential as a natural active ingredient for anti-aging cosmetic products, supported by its elastase and tyrosinase inhibitory activities and its stability and compatibility in cream formulations.